Technical Perspective 'What Is the Ideal Operating System?'. - Lohmann, Daniel (Communications of the ACM, 2022)
An introduction is presented in which the author discusses an article published in the journal about computer operating systems (OSs), particularly the practical aspects of the concept known as automatic kernel debloating.